Current Evidence on Associations of Nutritional Factors with Ovarian Reserve and Timing of Menopause: A Systematic Review. Issue 4 (6th July 2017) - Moslehi, Nazanin; Mirmiran, Parvin; Tehrani, Fahimeh Ramezani; Azizi, Fereidoun
ABSTRACT: Ovarian aging is thought to be influenced by environmental factors, including nutrition. The aim of this study was to systematically review current evidence on the associations between nutritional factors, ovarian reserve, and age at menopause. PubMed and Scopus were structurally searched until May 2016. Original studies, with either observational or interventional designs, that examined the associations of nutritional factors (serum or dietary nutrients, food groups, and/or dietary patterns) with different ovarian reserve markers and/or timing of menopause were considered eligible. Twenty-six studies met the inclusion criteria: 17 studies on ovarian reserve markers and 9 studies on menopausal age. Significant diversity was observed in nutritional factors examined across studies. In the study of nutritional factors, associations of serum 25-hydroxyvitamin D [25(OH)D] concentration and intakes of soy or soy products with ovarian reserve have been the most investigated. For associations with menopausal age, intakes of total fat, fiber, and soy products have been mainly examined. Significant associations with ovarian reserve markers were found in 4 of 7 studies on serum 25(OH)D, 2 of 6 studies on soy or soy products, 1 of 2 studies on fiber intake, 1 study on serum zinc and copper concentrations, and 1 study on serum antioxidant concentrations. Studies on nutritional factors and menopausal age provided inconsistent findings, some of which suggested modest associations. Although there is some promising evidence on the influential role of nutrition in ovarian aging, a limited number of studies, heterogeneous in their design and study of nutritional factors, makes it difficult to draw definite conclusions. To better understand this issue, examination of associations of dietary intakes or dietary patterns with more precise markers of ovarian reserve, such as anti-mullerian hormone and antral follicle count, with age at menopause is needed. In addition, to explore whether nutritional factors alter the process of ovarian aging, an examination of changes in ovarian reserve markers should be considered.